Pengembangan Media Pembelajaran Dasar-Dasar Teknik Jaringan Komputer dan Telekomunikasi berbasis Augmented Reality Untuk Siswa Kelas X SMKN 2 Paguyaman - I Made Yasa; Dian Novian; Arif Dwinanto; Mukhlisulfatih Latief; Abd. Aziz Bouty; Huzaima Mas’ud (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The development of information and communication technology has changed the world of education today. The lack of learning media used by teachers and the limitations of teaching aids have become problem in the learning process. This study aims to develop Augmented Reality-based learning media as a learning support tool and to determine their feasibility and practicality. This study employed the research and development method with the ADDIE model (Analyze, design, development, implementation, evaluation). The subjects consist of Grade X TJKT students at SMKN 2 Paguyaman. The instruments used to collect the research data included interviews, questionnaires, and documentation. The data analysis focused on the feasibility test and practicality tests of the learning media. The study’s findings show that the development of Augmented Reality-based learning media is successfully conducted through research and development, using the ADDIE development model. The results of the application feasibility test show a 96.6% value, indicating a very feasible category. Meanwhile, the students’ questionnaire results for the practicality test show an 88.55% score in the very practical category.